(untitled) - Loveland, Walter D. (Hoboken, N.J., 2006)
Modern Nuclear Chemistry provides up-to-date coverage of the latest research as well as examinations of the theoretical and practical aspects of nuclear and radiochemistry. Includes worked examples and solved problems.
Keywords: Nuclear chemistry,Hóa học hạt nhân